Clinical and prognostic differences among patients with light chain deposition disease, myeloma cast nephropathy and both. Issue 12 (2nd December 2015) - Zand, Ladan; Nasr, Samih H.; Gertz, Morie A; Dispenzieri, Angela; Lacy, Martha Q.; Buadi, Francis K.; Kumar, Shaji; Kyle, Robert A.; Fervenza, Fernando C.; Sethi, Sanjeev; Dingli, David; Rajkumar, S. Vincent; et al.
Abstract : In some patients with light chain deposition disease (LCDD) there is also evidence of myeloma cast nephropathy (MCN) on renal biopsy. The purpose of this study was to evaluate the renal and survival outcome of patients with concomitant diagnosis of MCN and LCDD to LCDD and MCN alone. Eighty seven patients were identified and divided into LCDD ( n = 45), MCN ( n = 29), and LCDD+ MCN ( n = 13). Patients with LCDD+ MCN had a worse overall survival (OS) compared to patients with LCDD ( p = 0.03), but similar to patients with MCN ( p = 0.4). Death-censored renal survival was no different amongst the groups. Presenting with acute renal failure at time of renal biopsy (HR 7.2, p = 0.0002) was an independent poor renal prognostic factor while older age (HR 1.06, p = 0.0002), presence of osteolytic lesions (HR 4.4, p < 0.0001), and requirement for dialysis or creatinine ≥ 5 mg/dL (HR 3.2, p = 0.0006) at time of renal biopsy were independent poor prognostic factors for OS.